Influence of difference length segmented Bi2Te2.95Se0.05/SnSe0.95I0.05 on thermoelectric's seebeck coefficient - Sallehin N.Z.I.M.; Nadhrah Md Yatim (American Scientific Publishers, 2024)
Indexed by Scopus/ERA